Efficacy of sacituzumab govitecan versus treatment of physician’s choice in previously treated HR+ and HER2− mBC: a meta-analysis of TROPiCS-02 and EVER-132-002 trials - Oleg Gluz; Binghe Xu; Rita Nanda; Anandaroop Dasgupta; Ankita Kaushik; Wendy Verret; Akanksha Sharma; Barinder Singh; Hope S. Rugo (Therapeutic Advances in Medical Oncology)
Background and objective: TROPiCS-02 and EVER-132-002 are phase III randomized controlled trials (RCTs) comparing sacituzumab govitecan (SG) to treatment of physician’s choice (TPC) in patients with hormone receptor-positive and human epidermal growth factor receptor 2 negative (HR+/HER2−) locally recurrent inoperable or metastatic breast cancer (mBC) who have progressed after two to four prior chemotherapy regimens. TROPiCS-02 enrolled mainly non-Asian patients, whereas EVER-132-002 consisted of only Asian participants. In this study, we compared the efficacy outcomes for SG to TPC via a meta-analysis of the two trials. Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses of Individual Participant Data (PRISMA-IPD) guidelines were followed. IPD from the trials were assessed for integrity, consistency, imbalances, or missing values and were combined to estimate pooled and relative treatment effects for comparison of overall survival (OS), progression-free survival (PFS), duration of response (DOR), objective response rate (ORR), and clinical benefit rate (CBR) in the overall, cyclin-dependent kinase 4/6 inhibitor (CDK4/6i) pre-treated, and fast-progressors population (defined as the subgroup of patients with duration of prior CDK4/6i ⩽12 months). Results: In general, TROPiCS-02 and EVER-132-002 had a similar distribution of baseline population characteristics except for prior CDK4/6i treatment and geography. In the overall meta-analytic model, SG showed a significant improvement over TPC in PFS (hazard ratio (HR), 0.62 (95% confidence interval (CI): 0.50–0.77); p  < 0.001) and OS (HR, 0.66 (95% CI: 0.55–0.80); p  < 0.001). Similar patterns in efficacy were observed in both fast-progressors as well as patients previously treated with CDK4/6i. In the overall population, SG was associated with statistically significantly higher ORR (rate ratio (RR), 1.45 (95% CI: 1.09–1.95); p  = 0.012), CBR (RR, 1.59 (95% CI: 1.28–1.97); p  < 0.001), and DOR (HR, 0.55 (95% CI: 0.32–0.95); p  = 0.032) compared to TPC. Conclusion: In conclusion, this meta-analysis confirms that SG significantly improves clinical outcomes in patients with HR+/HER2− mBC, including those pre-treated with CDK4/6i and fast-progressors when compared to TPC. These findings extend previous research, supporting the integration of SG into clinical practice guidelines at a global level for treating the HR+/HER2− mBC population irrespective of status and duration of prior CDK4/6i exposure.